Core topics in obstetric anaesthesia - MacLennan, Kirsty; O'Brien, Kate; Macnab, W. Ross (Cambridge : Cambridge University Press, 2015)
This new addition to the highly successful Core Topics in Anaesthesia series provides a clinically relevant text for both trainees and consultants, covering the entire sub-specialty of obstetric anaesthesia. In-depth coverage of pregnancy-related physiology and pharmacology makes this book an excellent revision tool for basic science examinations. It is also a troubleshooting guide for anaesthetists when managing parturients suffering with concurrent medical conditions including obesity, sepsis, hypertensive, renal, respiratory, neurological, haematological and endocrine diseases. Chapters provide recommended management plans for specific conditions such as HIV and neuropraxia following regional anaesthesia, and include algorithms to guide clinical decision-making. Guidance on the required infrastructure for setting up services such as antenatal clinics is also included. Experts in their fields have contributed sections including allergy testing and immunology, the immunocompromised parturient, and maternal collapse. This practical resource will serve as a survival guide for all those caring for parturients on the delivery suite.
Title from publisher's bibliographic system (viewed on 13 May 2016).